2023
DOI: 10.3390/microorganisms11020391
|View full text |Cite
|
Sign up to set email alerts
|

The Epibiotic Microbiota of Wild Caribbean Sea Urchin Spines Is Species Specific

Abstract: Caribbean sea urchins are marine invertebrates that have experienced a decline over the years. Studies on sea urchins have focused primarily on the microbiome of the coelomic fluid or the gut microbiota. In this study, the epibiota community associated with four wild Caribbean sea urchin species, Lytechinus variegatus, Echinometra lucunter, Tripneustes ventricosus, and Diadema antillarum, was characterized for the first time. Using 57 sea urchin animal samples, we evaluated the influence of animal species, tro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 83 publications
0
3
0
Order By: Relevance
“…Relevant contributions of bacteria belonging to Fusobacteriaceae and Planctomycetaceae were found in some individuals of O. validus collected in the Ross Sea area; these bacteria have been already found in association with other Antarctic marine organisms ( Webster and Bourne, 2007 ; Kim et al, 2020 ; Rodríguez-Barreras et al, 2023 ) and considered key players in global carbon and nitrogen cycles ( Olsen, 2014 ; Dedysh and Ivanova, 2019 ). Interestingly, our results indicated the presence of bacteria belonging to the Thermaceae family in some of our individuals of O. validus .…”
Section: Discussionmentioning
confidence: 97%
“…Relevant contributions of bacteria belonging to Fusobacteriaceae and Planctomycetaceae were found in some individuals of O. validus collected in the Ross Sea area; these bacteria have been already found in association with other Antarctic marine organisms ( Webster and Bourne, 2007 ; Kim et al, 2020 ; Rodríguez-Barreras et al, 2023 ) and considered key players in global carbon and nitrogen cycles ( Olsen, 2014 ; Dedysh and Ivanova, 2019 ). Interestingly, our results indicated the presence of bacteria belonging to the Thermaceae family in some of our individuals of O. validus .…”
Section: Discussionmentioning
confidence: 97%
“…The 16S ribosomal RNA (16S rRNA), present in all bacteria and archaea, serves as a molecular marker to identify and classify microbial taxa (Hakim et al, 2019). By analyzing the 16S rRNA gene sequences, researchers can unravel the intricate relationships between echinoderms and their associated microbial communities, shedding light on the potential roles of these microbes in echinoderm health, nutrition, and overall ecological functioning (Lima-Mendez et al, 2015;Rodríguez-Barreras et al, 2023). The 16S rRNA gene is a widely used molecular marker for studying microbial diversity and community structure.…”
Section: Prokaryotic 16s Metabarcodingmentioning
confidence: 99%
“…In addition to symbiotic interactions, 16S rRNA sequencing has provided insights into the dynamic nature of the microbiome in echinoderms. Studies have revealed variations in the microbial community composition across different developmental stages, habitats, and environmental conditions (Ketchum et al, 2021;Marangon et al, 2023;Rodríguez-Barreras et al, 2023). These findings suggest that the echinoderm microbiome is influenced by both intrinsic factors and extrinsic environmental factors, highlighting the importance of considering the context-dependent nature of microbial associations in echinoderm research.…”
Section: Prokaryotic 16s Metabarcodingmentioning
confidence: 99%